The Compilation of College Students’ Mental Huagong Scale Based on Chinese Culture - Li, Li Bing-quan; Wu, Run-miao; Mai, Zhen-ke (Technium Social Sciences Journal, 2023)
Chinese culture contains rich positive thoughts of mental transformation, mentcal Huagong(MHG: 心理化功) is the embodiment of people’s quality of psychological transformation. MHG refers to the Gongfu(功夫) or mental competence that transforms negative or passive into positive or advantageous mind, which is an indispensable quality for contemporary people, especially college students, to find favorable position for the use of their abilities(用武之地) in society. In order to understand the level of college students’ MHG, 586 college students from ordinary universities in Guangdong Province were tested. By item analysis and exploratory factor analysis on sample 1, confirmatory factor analysis on sample 2, college students’ mental Huagong scale(CSMHGS: 大学生心理化功量表) was compiled finally. The result shows that CSMHGS is composed of 35 items and 5 factors, and the cumulative variance contribution rate is 56.145%. The result of confirmatory factor analysis shows that the 5-factor model fitted well. Cronbach α coefficient of the total scale is 0.854, and the reliability coefficient of each dimension of the scale is between 0.809 0.856. It is concluded that CSMHGS has good reliability and validity, and can be used as a measuring tool for the study of college students’ MHG.